Effect of Type 1 and Type 2 Diabetes Mellitus on Complication and Reoperation Rates of Ankle Arthrodesis and Total Ankle Arthroplasty. Issue 3 (14th September 2018) - Tucker, William; Morris, Brandon; Tarakemeh, Armin; Mullen, Scott; Schroeppel, Paul; Vopat, Bryan
Category: Diabetes Introduction/Purpose: Diabetes mellitus (DM) poses a risk for increased rate of complications in many orthopaedic procedures, especially in patients undergoing elective arthroplasty procedures. Treatment of end-stage ankle arthritis includes both arthroplasty and arthrodesis. Current literature provides minimal guidance regarding outcomes of total ankle replacement (TAR) or ankle arthrodesis (AA) in diabetic patients. The authors of this study utilized a large database to compare rates of postoperative complications and reoperations of diabetic patients undergoing surgical management of ankle arthritis to rates seen in non-diabetic patients. Methods: Using the PearlDiver Technologies, Inc. database, Medicare patients diagnosed with ankle arthritis using ICD-9 codes were identified from 2005 to 2014. Patients were then sorted as diabetic or non-diabetic. Diabetic patients were then further stratified into Type 1 diabetes (T1DM) and Type 2 diabetes (T2DM). Type 2 diabetics requiring insulin (T2ID) and not requiring insulin (T2NID) were also isolated. Patients were identified who underwent either AA or TAR utilizing ICD-9 procedure and CPT codes. These groups were evaluated for postoperative complications and reoperation rates. Chi-Squared testing was used to determine significance. Multivariate analysis was performed to determine whether diabetes represents an independent risk factor. Results: 1477 diabetic patients underwent TAR and 5399 underwent AA versus 3900 TAR and 7838 AA in nondiabetics. Diabetics undergoing AA experienced complications at 32.2%, reoperations at 30.8%, and revisions at 18.7% versus 13.3%, 22.3%, and 19.2% respectively in patients without diabetes(P<0.05). In diabetics undergoing TAR, the complication rate was 21.6% and reoperation rates were 16.9% versus 12.5% and 13% respectively in their non-diabetic counterparts(P<0.05). Revision rates were similar. Patients with T1DM had more reoperations and complications in both TAR and AA compared to those with T2DM (P<0.05). In both surgical groups, Patients with T2ID had more complications and reoperations than those with T2NID(P<0.05). Multivariate analysis revealed diabetes as an independent risk factor for complication and reoperation in AA but only complication in TAR(P <0.05). Conclusion: Patients with a diagnosis of diabetes mellitus experienced higher complication and total reoperation rates when undergoing either TAR or AA. T1DM appears to impart a greater risk of surgical complication and repeat surgical intervention than does T2DM. However when insulin is required in T2DM, complication and reoperation rates are similar to those of T1DM. Patient selection for surgical management of end-stage ankle arthritis should incorporate diabetic type and insulin dependency when considering surgical intervention.